2017
DOI: 10.18632/oncotarget.22910
|View full text |Cite
|
Sign up to set email alerts
|

Leucine mediates autophagosome-lysosome fusion and improves sperm motility by activating the PI3K/Akt pathway

Abstract: Amino acid supplementation is an efficient and effective strategy to increase sperm quality. In our research, a comparative study was conducted to screen free amino acids to improve sperm motility, and we found that leucine was the most efficient one. Leucine treatment increases sperm motility depending on the activation of PI3K/Akt signaling pathway, while the chemical inhibitor of PI3K/Akt signal could reduce the amount of pAkt activated by leucine treatment. Moreover, leucine treatment improved the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
3
27
0
Order By: Relevance
“…Leucine concentration in SP was found to be positively correlated with the percentage of viable sperm with a non-intact acrosome (P = 0.038) and negatively associated with the loss of total (P = 0.039) and progressive (P = 0.024) motility after 72 h of liquid storage. Despite the fact that no information regarding leucine effect on sperm performance is available in mammals, the addition of this metabolite is known to have a positive effect on the motility of zebrafish sperm (Zhang et al, 2017). Similarly, our findings revealed that hypotaurine concentration in SP was negatively related with higher loss of progressive motility (P = 0.018) after liquid storage at 17 • C. In this context, it is worth mentioning that hypotaurine supplementation has been reported to exert a positive impact upon sperm motility in mammalian species, such as hamsters (Boatman et al, 1990) or humans (Holmes et al, 1992;Brugnon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Leucine concentration in SP was found to be positively correlated with the percentage of viable sperm with a non-intact acrosome (P = 0.038) and negatively associated with the loss of total (P = 0.039) and progressive (P = 0.024) motility after 72 h of liquid storage. Despite the fact that no information regarding leucine effect on sperm performance is available in mammals, the addition of this metabolite is known to have a positive effect on the motility of zebrafish sperm (Zhang et al, 2017). Similarly, our findings revealed that hypotaurine concentration in SP was negatively related with higher loss of progressive motility (P = 0.018) after liquid storage at 17 • C. In this context, it is worth mentioning that hypotaurine supplementation has been reported to exert a positive impact upon sperm motility in mammalian species, such as hamsters (Boatman et al, 1990) or humans (Holmes et al, 1992;Brugnon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine inhibits the process of degradation of the autophagosome-lysosome, blocking the normal process of autophagy. This inhibition leads to the accumulation of LC3 within the cell and inhibits the degradation of P62, which down-regulates the autophagy level [35,36]. Under the electron microscope, we observed that chloroquine inhibits the process of degradation of macrophage autophagosome-lysosome and decreases the expression of LC3 and Beclin-1 and increaseds the expression of P62.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated RNA was reverse transcribed into cDNA was by Prime Script TM RT reagent Kit with gDNA Eraser (Stratagene, Takara). Real-time PCR was performed on ABI-7500 real-time PCR machine (Applied Biosystems, USA) and β-actin was used to normalize the expression values(67). The primer sequences used in qRT-PCR are listed in tables 1, 2, and 3.…”
Section: Methodsmentioning
confidence: 99%